Knowledge Dynamics in Sustainable Standard Setting in Tourism - The case of "Fair Trade in Tourism South Africa (FTTSA)" - Simone Strambach; Annika Surmeier (Philipps-University Marburg, Department of Geography, 2012)
The development of standards and certification programs in global tourism has gained importance in consumption-production nexus. The paper is dealing with 'Fair Trade in Tourism South Africa' (FTTSA), one of the first innovative service standards with a focus on the social dimension of sustainability. Until now, there has been little detailed exploration in the evolutionary trajectories of sustainable tourism standards from a knowledge-based perspective. This paper will contribute to a deeper understanding of the standard creation in global-local interaction processes over time and its impacts on the micro level of the firms. Conceptually it builds on two scientific debates - the neo-institutional approaches in organizational theory focussing on institution building and the research on innovation and knowledge dynamics. Empirically, it is based on 32 interviews conducted with different actor groups.
Keywords: D83; L83; O55; P48; Q56; 330; Knowledge Dynamics; Sustainable standards; Institutional theory; South Africa; Tourism